“Хуторянство” Пантелеймона Куліша як український екзистенціалізм - Юдкін-Ріпун, І. (Студії мистецтвознавчі, 2008)
One has not still invented an adequate key to interpret the philosophy of history of P. Kulish. It continues the tradition of anti-urban critics initiated in the Jeremiah’s prophecy of the Holy Bible. An important role has played here the so called resurrectionist movement where the notions of the “philosophy of vitalism” were reinterpreted within the framework of the christian concept of revival.